Configuration Comparison Catenary Spread Mooring Line On The Movement Characteristics Of Fpso Ships Using Numerical Analysis - Julyardiansyah, Fadhil; Assidiq, Fuad Mahfud (Maritime Park: Journal of Maritime Technology and Society, 2024)
Abstract: FPSO (Floating Storage Production and Offloading) is a floating structure that can be used as a location for production, storage or offloading of offshore oil and gas. Therefore, FPSO plays an important role in the exploration of oil fields in the deep sea. When operating, the FPSO will be exposed to environmental loads that can cause it to operate flexibly. To reduce movement response and maintain the FPSO in position, a mooring system is needed. The aim of this research is to analyze the numerical results of this experiment to find RAO (Response Amplitude Operator) free movement (free floating) as well as motion trajectory (surge & sway), motion characteristics, mooring line stress based on variations in the number of ropes used when moored with the direction of loading (heading) from different directions with time domain 250 seconds for each identification. This comparison analysis uses software Boundary Element Method (BEM) with data on FPSO dimensions, type of rope and mooring system, as well as environmental loads that influence the movement of the FPSO structure. The results of the analysis obtained show that in essence the use of the number of mooring lines will greatly influence the movement characteristics, the trajectory/flow of the floating structure and the tension of the mooring ropes. Where, the fewer the number of ropes used, the greater the movement and tension of the resulting rope and vice versa. Usually due to the mass of mooring line which is influenced by the number of ropes not being the same or smaller than displacement FPSO and is also influenced by environmental forces or loads which have repeated patterns over a certain time so that the amount used mooring line must also consider all aspects of the environment in its planning.